Verletzungen beim Dinghysegeln bei Anfängern: Eine Analyse - Schaefer, O. (Sportverletzung Sportschaden, 2000)
In the sailing season of 1998 536 students have been assigned to a study investigating injuries that happened during beginners courses of dinghy-sailing. They were advised to document all injuries even minor ones and their circumstances while being on the boat. Injuries of the upper extremities were found in 39.5%, the head was affected in 32.4%, the lower extremities was injured in 26.5% and 1.6% had injuries of neck and/or trunk. Various types of injuries were observed: contusions in 55.1%, graze of skin in 17.2%, cuts and tears in 14.3%, bruises in 6.3%, tender spots, blisters and callus in 4.6%, lacerations in 1.7%, pulled muscles in 0.4% and fractures were seen in 0.4%. Typical situations in which injuries occurred were the collision with the main boom (31.1%), the rigging up and down (13%), capsizing (10.50%), docking and casting off (9.7%), the handling of the sheets (9.2%), the conditions in the harbour (8.8%) and slipping while onboard (6.8%). It becomes apparent that contusions and gazes of the head are caused by the standing rigging in contrast to skin-graze, lacerations, cuts and bruises which are rather caused by the running rigging. There is a higher risk of injuries for the helmsman than for the foredeckhand. However the incidence is evenly distributed among the sexes. Moreover there are significant differences in the accident rate concerning the direction and the strength of wind. Stronger and onshore winds make the sailor more accident-prone.